Pakistan - Operational Design for the Project Development Fund and for the Viability Gap Fund - World Bank (Washington, DC, 2013)
This final report is the fifth deliverable for the World Bank funded project 'operational design for the project development fund and for the viability gap fund'. Taking into account feedback and further consideration of issues rose in the previous Reports, it aims to: provide high level recommendations on the overall Public Private Partnership (PPP) framework in Pakistan, recognizing international best practice but also taking into account the specific Pakistan context and the challenges faced their-in; provide the analysis of the project pipeline for PPP projects in Pakistan, on the basis of consultations undertaken in Islamabad in May 2009; and design possible structures for the Project Development Fund (PDF) and for the Viability Gap Fund (VGF), that is informed by the current local enabling environment for PPPs, including the institutional capabilities and the existing pipeline of PPP projects. This final report incorporates feedback from the World Bank and the Government of Pakistan on each of the above-listed issues, which were set out and discussed in details in previous reports.